Individual Account of Rotor Current Displacement while Calculating Group Self- Starting of Asynchronous Electric Motors Being TPS Auxiliaries - V. I. Novach; R. F. Minachev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers the possibility to make calculation of group self-starting of asynchronous electric motors being TPS auxiliaries with the help of generalized (averaged) dependences Kr{s), Kx{s) which are equal for all electric motors involved in self-starting process and which makes it possible to take into account displacement of rotor current. Generalized dependences have been obtained on the basis of individual dependences using method of least squares with due account of utilization of these or that characteristics. The paper provides results of the calculations in respect of individual and averaged characteristics of a number of motors. It is concluded that there is possibility to use averaged characteristics for calculation of motor group self-starting.